Προσομοίωση της ενεργειακής κατανάλωσης κτιρίου με την χρήση σκιάστρων/προβολών σε διαφορετικούς προσανατολισμούς - Χαραλάμπους, Ανδρέας (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This thesis entitled "Simulation of energy consumption in buildings with the use of sunshields". In this dissertation the appropriate software (IES-VE Software) was used for simulating a specific room/model with specific characteristics by applying to it 5 different types of window sunshields. Since many types of sunshields can be found in the market, some of the most widely known and used in buildings were chosen. Initially, the legislation pertinent in effect in the Republic of Cyprus on energy issues was briefly introduced. Subsequently, a survey of the relevant literature on similar studies pertaining to different shading systems is presented. This is followed by a description of the software that was used for the simulations, as well as the different characteristics of the model that will be subsequently examined. Reference is also made to the nature of the simulations that will be described in subsequent chapters. Subsequently, the outcomes of the simulations as well as the main conclusions that were drawn are discussed. More specifically, the heating and cooling loads of the model are analyzed along with the differences that emerge due to the combination of orientations with different types of sunshields. Finally, the general conclusions of this dissertation and suggestions for potential future research activities in this area are presented.
Keywords: IES-VE Software; Σκίαση